Highly significant antiviral activity of HIV-1 LTR-specific tre-recombinase in humanized mice. - Ilona Hauber (Public Library of Science (PLoS), 2013)
Stable integration of HIV proviral DNA into host cell chromosomes, a hallmark and essential feature of the retroviral life cycle, establishes the infection permanently. Current antiretroviral combination drug therapy cannot cure HIV infection. However, expressing an engineered HIV-1 long terminal repeat (LTR) site-specific recombinase (Tre), shown to excise integrated proviral DNA in vitro, may provide a novel and highly promising antiviral strategy. We report here the conditional expression of Tre-recombinase from an advanced lentiviral self-inactivation (SIN) vector in HIV-infected cells. We demonstrate faithful transgene expression, resulting in accurate provirus excision in the absence of cytopathic effects. Moreover, pronounced Tre-mediated antiviral effects are demonstrated in vivo, particularly in humanized Rag2⁻/⁻γc⁻/⁻ mice engrafted with either Tre-transduced primary CD4⁺ T cells, or Tre-transduced CD34⁺ hematopoietic stem and progenitor cells (HSC). Taken together, our data support the use of Tre-recombinase in novel therapy strategies aiming to provide a cure for HIV.